2019
DOI: 10.1021/acs.nanolett.9b01652
|View full text |Cite
|
Sign up to set email alerts
|

A New Organic Interlayer Spacer for Stable and Efficient 2D Ruddlesden–Popper Perovskite Solar Cells

Abstract: Two-dimensional (2D) perovskite materials have exhibited great possibilities toward the fabrication of highly efficient and stable solar cell devices. The large degree of structural versatility due to the viable choices of organic interlayer spacers promises new and valuable 2D perovskite species. Herein, phenyltrimethylammonium (PTA+) is successfully employed as the organic interlayer spacer to prepare the 2D Ruddlesden–Popper perovskite films that exhibit exceptional optoelectronic properties. By adding Cl– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 43 publications
6
77
0
Order By: Relevance
“…[25,35] To probe the structure and spatial distribution of the PA + and PDA 2+ containing substances in the RbCsFA films, the GI-XRD measurements are conducted. [36][37][38] The X-ray penetration depth in the perovskite films can be tuned by adjusting the incident angle. The X-ray incident angle is set to 0.05° and 1° to probe the shallow surface and full-depth structures of the perovskite films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[25,35] To probe the structure and spatial distribution of the PA + and PDA 2+ containing substances in the RbCsFA films, the GI-XRD measurements are conducted. [36][37][38] The X-ray penetration depth in the perovskite films can be tuned by adjusting the incident angle. The X-ray incident angle is set to 0.05° and 1° to probe the shallow surface and full-depth structures of the perovskite films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are only several reports about planar n‐i‐p RP perovskite‐based PSCs, most of them utilized metal oxides including TiO 2 and SnO 2 as the underlying layer to support the growth and formation of high‐quality RP perovskite films. [ 169,197 ] It is thus safe to conclude that the underlying charge transporting layer should be carefully selected via integrating the surface wetting capability into account since this property determined whether the RP perovskite films have full and continuous coverage. This does not mean that other properties such as charge transporting capability and the energy level alignment of the underlying transporting can be neglected.…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…Fortunately, the addition of MACl or NH 4 Cl into the precursor solution greatly improved the film quality. [ 124,168,169 ] Figure shows GIWAXS patterns and SEM images of (PTA) 2 (MA) 3 Pb 4 I 13 and (ThMA) 2 (MA) 2 Pb 3 I 10 films modified by different amounts of MACl. By tailoring the amount of MACl, (PTA) 2 (MA) 3 Pb 4 I 13 films presented vertical‐orientated 2D perovskite QWs as well as dense and flat surface with micrometer‐scale crystal grains, while (ThMA) 2 (MA) 2 Pb 3 I 10 films showed a unique nanorod‐like morphology with increased crystal size and improved out‐of‐plane crystallization orientation.…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…However, it is worth noting that the perovskite materials in most optoelectronic devices, even the best PSC or LED, are still polycrystalline [11,12]. The efficiency or property of perovskite optoelectronic devices is limited by nonradiative recombination, which is caused by a large number of defects in polycrystalline films [11][12][13][14]. Reports have demonstrated that perovskite single crystals have significantly higher carrier mobility and longer carrier lifetime compared with polycrystalline, due to their extremely low defect state density and high crystallinity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with polycrystalline films, the perovskite film composed of many high-quality crystalline grains not only retains the advantages of single crystals but also is more suitable for the structure of optoelectronic devices. Phenethylammonium (PEA), a commonly used additive for passivating defects and preparing two-dimensional perovskite [11,13,14,[35][36][37][38], has a molecular structure similar to PMA. However, the introduction of PEA + to prepare perovskite films composed of single crystals has not been reported.…”
Section: Introductionmentioning
confidence: 99%